Stanislaw Lem, tra scienza ‘dura’ e letteratura - Moretti, Giampiero (Itinerari, 2024)
In his article, the Author takes inspiration from Stanislaw Lem’s initial studies on natural sciences, and in particular cybernetics, in order to reflect on the role that they have played in his literary journey. Consideration is given to the stochastic process whose role Lem believed to be critical in the development of the notion of “chance” and “probability”. In his novel Solaris, as well as in others, such notion does not morph into a generic exaltation of Chaos, but rather into the examination of the modality in which a chain of events occurs. Particular attention is given to the dispute between Lem and the Noveau Roman.